(untitled) (Research, Society and Development, 2020)
Adolescence is a period between the age of 10 and 20 years, according to the World Health Organization. With the exercise of sexuality, the beginning of early sexual activity among adolescents has great implications, even becoming a public health problem. The aim of this study was to investigate through integrative literature review (RIL) the degree of knowledge of adolescents in relation to STIs/AIDS. For the analysis, we used articles published in electronic databases of the last 10 years, providing important information on the subject. The findings revealed that adolescents are aware of acquired immunodeficiency (HIV/AIDS) as well as their prevention measures, but it is still a group considered vulnerable to this and other sexually transmitted infections, and it is necessary to advance health promotion actions, since the infection rate is still high among the group. Thus, the development of public policies that promote health promotion and prevention actions are extremely relevant for the reduction of these indicators and for the improvement of the quality of life of this group.